Tissue depletion of azaperone and its metabolite azaperol after oral administration of azaperone in food-producing pigs - Mestorino, Olga Nora (2013)
Azaperone is a butyrophenone tranquilizer for swine. Food producing pigs are particularly sensitive to stress during handling and transport to the abattoir. In vivo, azaperone is partially metabolised to azaperol, a metabolite with pharmacological activity. The high and persistent concentrations of azaperone and azaperol in the injection site contra-indicates the use of azaperone using the intramuscular route for the transport of the food producing animals, pigs, to the slaughterhouse; the oral use could be an alternative to avoid residues at the injection site. The present study determined the tissue depletion of azaperone and its metabolite azaperol after oral administration of the formulation Stresnil®. Male pigs (30-45 kg of body weight) were treated with Stresnil® (single oral dose of 4 mg azaperone/kg body weight) and were sacrificed 6, 24 and 48 hours after the administration. Muscle, skin + fat, liver and kidney were collected from each animal. Azaperone and azaperol were assayed by HPLC after solid phase extraction. The concentrations of the azaperone plus azaperol in all analysed tissues did not exceed to the Maximum Residue Limit (MRL) established by the European Union (100 μg/kg in muscle, liver, kidney and skin plus fat) at any sampling time. As a consequence, from the results obtained in the present study, edible tissues of pigs treated orally with 4 mg/kg azaperone, 6 hours before to the sacrifice, might be acceptable to guarantee safety for the consumers. Nevertheless a withdrawal time of cero hours was estimated by linear regression analysis.